S143 The sensations provoking cough: a qualitative investigation. (2nd December 2011) - Solari, F; Sunger, K; Yorke, J; Caress, A; Smith, J A
Abstract : Background: Little is known about the sensations patients feel prior to or that provoke their cough. Aims: To identify, from the patient's perspective, key descriptors that relate to the sensations provoking cough in patients diagnosed with one of the following: idiopathic cough, asthma, chronic obstructive pulmonary disease (COPD), fibrotic interstitial lung disease (ILD) and cystic fibrosis. Methods: One-to-one, audio recorded, semi- structured interviews were conducted with 34 participants (7 idiopathic cough: age 40–69 years, 5 female, 6 asthma: age 42–65 years, 5 female, 7 COPD: age 52–86 years, 2 female, 7 ILD: age 58–79 years, 3 female, 7 cystic fibrosis: age 20–39 years, 2 female). Words and phrases relating to 1 of 8 top level codes, derived from the interview topic guide (triggers, sensation, sputum, emotion, location, frequency, time and relief) were extracted using simple manifest content analysis. These descriptions were then organised into similar themes. Relationships between the descriptions and themes both within and between the groups were explored. Results: All groups described the sensation of a "tickle" or an "irritation" that was felt most in the throat and upper chest. Cystic fibrosis and COPD participants most commonly described feeling a "need to clear" their airways. The ILD group mostly described a "dry", "tickly" sensation. The idiopathic cough and asthma groups used a very heterogeneous set of terms regarding the sensations provoking their cough. Common across the groups is a hypersensitive response to things that may trigger their urge to cough and all groups described coughing as relieving that urge. Emotionally the sensation is associated with negative emotions, however positive feelings were also described; by some who described feeling a need to clear their airways. Conclusion: The extracted list of descriptions has provided some insight into what the sensations provoking cough feel like from patient's perspective and suggest that the sensations felt relate to the pathology of the individual's diagnosis. The distinction between the need to clear and a sensation of a tickle or irritation could be important in understanding the mechanisms driving cough and may be important for the development of targeted interventions.